Teachers' Opinion about Implementation of the Professional Standard: Results of Sociological Research - Margolis A.A; Arzhanykh E.V; Gurkina O.А; Novikova E.M (Moscow State University of Psychology and Education, 2016)
The article discusses some aspects of the teaching community readiness to implementation of the professional standard. Based on the questionnaire data, conducted among teachers of educational institutions in all federal districts of the Russian Federation (1000), the authors estimated the level of teachers' awareness about the professional standard, as well as related to its implementation. Although the implementation of the professional standard is expected in the nearest future, this research shows that the level of awareness of teachers it is not high enough. Not all teachers reviewed this document, and among respondents who claimed to have studied the standard, a considerable percentage doesn't know, what information is contained in it. In general, respondents are positive about the inmpementation of professional standards, although there are concerns among educators that bureaucratic barriers on them may increase.